The Effectiveness Of Quantum Learning To Increase Motivation And Mastery Of Arabic Vocabulary Of Learners - Munawarah Munawarah; Haniah Haniah; Kamaluddin Abunawas (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2020)
This research aims to see the difference in the effectiveness between the quantum learning model at the experiment class and TPS (think pairs share) model at the controlling it is observed from the learning motivation and mastering the students' Arabic Language vocabulary. This research uses the quantitative method, which is quasi-experiment. The data collection method is a questionnaire, test, and observation with independent sample t-test data analysis. This research collects data and serves it systematically by using SPSS 22 for windows application. The results showed that quantum learning models in practical classes and TPS learning models (think pairs share) in control classes are classified as useful because they increase average value. This indicates that using various learning models can increase the motivation and mastery of learners' Arabic vocabulary so that educators do not just monotonously apply one model in learning. Educators are also required to use many models (multi-methods) because varied learning models can positively influence increasing motivation and mastery of Arabic vocabulary.